Wise Socialization In Use Technology And Information: Sosialisasi Bijak Dalam Menggunakan Teknologi Dan Informasi - Emi handrina; Gusnayetti (KPN Kopertis X, 2023)
This Community Service project aims to provide smart and wise socialization in using technology and information, as it can have a significant positive impact on the development and application of science in society. The project is entitled